MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA MATA PELAJARAN PKN UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI SD: KAJIAN PUSTAKA - Aulia Khairin; Endang Noerhartati; Octavia Shellma Aureola; Eryeke Rifda Sholikhatul Liza; Nanda Nicola Syah Poetra (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Education is an effective means in educating the nation's life, this is one form of implementing the third goal of the Indonesian state, namely the intellectual life of the nation. To obtain good educational results, it should be supported by a good learning process by using various appropriate models and methods so as to be able to achieve learning objectives optimally. Problem based learning is a model that can increase students' attention, abilities and activities so that they can construct knowledge as part of understanding a concept in learning. This study uses a qualitative approach with a descriptive method. Sources of data used in the form of previous research journals that answer research questions under study and supported by secondary data obtained from other literature. The method of data collection is done through documentation and literature study. The data analysis technique uses source triangulation in the form of searching for data from different sources of journals and libraries to ensure the validity of the data. The results of the study show that the objectives of civics learning, namely smart.